How to Measure Rhetorical Impact of Teaching and Their Levels of Persuasion: A Neuro-Rhetoric Approach - Cordova-Gonzalez, F; Palominos-Villavicencio, F; Canete-Arratia, L; Diaz-Munoz, H (Springer Science and Business Media Deutschland GmbH, 2015)
This paper explore the question about how persuasive is a person, a professor in our interest, depending on his/her rhetoric. Since persuasion is an act for amending the mind, a model to describe this intellectual entity in students consists of seven categories of elements in it: Quality, Quantity, Space, Time, Causality, Purpose and Law. According to the emphasis that the persuader places in each category of mental elements, he/she is classified in a rhetorical manner. The effect over the system of beliefs of a student caused by each rhetoric manner will be different depending on the way the new paradigm confront older or misunderstood previous classifications, organizations, and conceptualizations. Since the processing of a discourse occur mentally, not necessarily expressed by notorious disturbances in the behavior, we explore the way to measure the attentional impact of two lecturer: (i) a human being; and (ii) a computer machine, on the EEG activity of three listeners. We extracted the upper 25 % of EEG signal intensity for the whole frequency 0.1–64 Hz range, to proceed to analyze the graphical data extracted from the time/frequency/intensity EEG spectrograms. Additional and supplementary on-field results indicate that teachers who prefer affect Causalities, Purposes and Laws; are the most persuasive. © 2015, Springer-Verlag Berlin Heidelberg.